2018
DOI: 10.1159/000495275
|View full text |Cite
|
Sign up to set email alerts
|

6- and 8-Prenylnaringenin, Novel Natural Histone Deacetylase Inhibitors Found in Hops, Exert Antitumor Activity on Melanoma Cells

Abstract: Background/Aims: Prenylnaringenins are natural prenylflavonoids with anticancer properties. However, the underlying mechanisms have not been elucidated yet. Here we report a novel mode of action of 6- and 8-prenylnaringenin (PN) on human melanoma cells: Inhibition of cellular histone deacetylases (HDACs). Methods: We performed in silico and in vitro analyses using 6-PN or 8-PN to study a possible interaction of 6-PN or 8-PN with HDAC as well as Western blot and FACS analyses, real-time cell proliferation and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 38 publications
4
22
0
Order By: Relevance
“…This property prevents the formation of 8-PN, one of the most potent phytoestrogens known (Figure 1) [3,20,21]. Interestingly, 8-PN possesses anti-proliferative effects in vitro against the colon carcinoma cell line Caco-2, breast carcinoma line MCF-7, the melanoma line SK-MEL-28, and a Burkitt lymphoma cell line [21,22,23,24,25]. The estrogenic effects of 8-PN also show promising clinical results in treating postmenopausal symptoms, but these studies are usually short term and were not designed to assess the effect of potential cancer promoting properties [26].…”
Section: Introductionmentioning
confidence: 99%
“…This property prevents the formation of 8-PN, one of the most potent phytoestrogens known (Figure 1) [3,20,21]. Interestingly, 8-PN possesses anti-proliferative effects in vitro against the colon carcinoma cell line Caco-2, breast carcinoma line MCF-7, the melanoma line SK-MEL-28, and a Burkitt lymphoma cell line [21,22,23,24,25]. The estrogenic effects of 8-PN also show promising clinical results in treating postmenopausal symptoms, but these studies are usually short term and were not designed to assess the effect of potential cancer promoting properties [26].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, 6-PN and a standardized hop extract selectively induced upregulation of AhR-dependent estrogen detoxification pathway by reducing of DNMT1-mediated inhibition of CYP1A1 transcription [ 228 ]. Moreover, Venturelli et al [ 229 ] have shown by in silico studies that both 6-PN and 8-PN can fit into catalytic site of HDAC 2, 4, 7 and 8 enzymes and interact with Zn ion for catalytic activities, so may be acting as pan-HDACs inhibitors. The in vitro experiments revealed that 6-PN and 8-PN can induce a rapid hyperacetylation of H3 histone within few hours after applying the PFs treatment on melanoma cells.…”
Section: Epigenetic Modulator Capacity Of Dietary Phytoestrogensmentioning
confidence: 99%
“…In addition, the effects of C15 urushiol and its triazole derivatives on the apoptosis of liver cancer cells have been qualitatively and quantitatively verified ( 132 ). Venturelli et al ( 133 ) reported that 6- and 8-prenylnaringenin enter into the 'foot pocket' of HDAC2 and combine with zinc ion of their catalytic center, subsequently inhibiting excessive proliferation of melanoma cells. N-[4-(Hydrazinecarbonyl)phenyl]-3,5,6-trimethylpyr- azine-2-carboxamide exhibits notable anticancer activity in vivo (IC 50 =1.60 μ M) ( 134 ) Among squaramide-based derivatives, the lead compound 42 exhibits good druggability by specifically inhibiting HDAC2 ( 67 ).…”
Section: Hdac2 In Liver Diseasementioning
confidence: 99%